2001
DOI: 10.1034/j.1600-0412.2001.800703.x
|View full text |Cite
|
Sign up to set email alerts
|

Levels of dimethylarginines and cytokines in mild and severe preeclampsia

Abstract: Plasma concentrations of both asymmetric and symmetric dimethylarginine were significantly elevated both in mild and severe preeclampsia. Symmetric, but not asymmetric, dimethylarginine correlated to the severity of the condition. Plasma levels of interleukin-6 and -8 were also elevated in severe preeclampsia but no direct correlations were found between these cytokines and dimethylarginines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
33
2
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 36 publications
9
33
2
1
Order By: Relevance
“…In pregnant SLE women, IL-6 serum concentrations were higher than in controls with a peak in the first trimester, 43 while IL-10 resulted persistently higher in patients with SLE, both before and during pregnancy. 47,48 In conclusion, the present findings showed an increased cytokine profile in pregnant women with SLE, with high levels of Th17 and activin A suggesting a possible contribution of placenta to immune adaptation in the pregnant SLE women. 47,48 In conclusion, the present findings showed an increased cytokine profile in pregnant women with SLE, with high levels of Th17 and activin A suggesting a possible contribution of placenta to immune adaptation in the pregnant SLE women.…”
Section: Discussionsupporting
confidence: 58%
“…In pregnant SLE women, IL-6 serum concentrations were higher than in controls with a peak in the first trimester, 43 while IL-10 resulted persistently higher in patients with SLE, both before and during pregnancy. 47,48 In conclusion, the present findings showed an increased cytokine profile in pregnant women with SLE, with high levels of Th17 and activin A suggesting a possible contribution of placenta to immune adaptation in the pregnant SLE women. 47,48 In conclusion, the present findings showed an increased cytokine profile in pregnant women with SLE, with high levels of Th17 and activin A suggesting a possible contribution of placenta to immune adaptation in the pregnant SLE women.…”
Section: Discussionsupporting
confidence: 58%
“…That ADMA levels are higher than normal in preeclamptic patients supports this idea. 12,13 Our findings differ from those of Holden et al," who reported that during a normal pregnancy maternal plasma ADMA reaches a minimum by the end of the first trimester, then increases with increasing gestational age. In addition, they found that the plasma ADMA concentration correlated significantly with blood pressure at all stages of normal pregnancy and that changes in the level of circulating ADMA contribute significantly to the changes in blood pressure seen in both normal and preeclamptic pregnancies.…”
Section: Discussioncontrasting
confidence: 99%
“…Increase of ADMA in endothelium-dependent vascular dysfunction was detected in diabetic, hypertensive, and hypercholesterolemic patients [20, 47, 48]. It is reported that ADMA may decrease at the beginning of normal pregnancy [49], but under the preeclampsia condition its concentration increases [5052], which may be associated with the disease intensity [50]. It seems that ADMA is involved in preeclampsia pathogenesis because inhibition of NO synthesis in rodents during pregnancy produces signs similar to those of preeclampsia [5355].…”
Section: Discussionmentioning
confidence: 99%